The Effect of Using Puzzle Media on Activity and Learning Outcomes of Class III MIN Students in Indragiri Hulu Regency - Suryani Samaun, Yeni (The Future of Education Journal, 2023)
This study began with observations made in class III MIN 1 Indragiri Hulu, the teachers only use conventional media in SKI Learning, student learning activities that tend to be passive so that it impacts on student learning outcomes that have not yet reached the minimum completeness citeria. The use of Puzzle media in learning can improve students’ learning activities and learning outcomes. This study aims to explain the effect of the use of Puzzle media on the activities and learning outcomes of SKI class III MIN in Indragiri Hulu Regency. The type of research used is Quasi Experiment. The population in this study were all students of class III MIN in Indragiri Hulu Regency. The research sample class III A as an experimental class and class III B as a control class in MIN 1 Indragiri Hulu. Sampling is done randomly (randomly) using a lottery. Research data were collected through activity observation sheets and student learning outcomes using t-test. Based on the research findings and the discussion concluded as follows. First, there is a significant difference in activities for students who are taught using the media puzzle with learning activities of students who are taught using picture media in class III MIN SKI learning in Indragiri hulu Regency. Based on the calculation, the t value is 1.894 with a significant level of 5% is 1.682, the price of t is greater than t table so Ha is accepted. Secondly, there are significant differences in learning outcomes for students tagught using image media in the class III MIN SKI learning in Indragiri Hulu regency. Based on the calculation, the t value is 2.202 with a significant level of 5% is 1.682, the price of t is greater than t table so Ha is accepted